A review of the predictive role of functional imaging in patients with mucosal primary head and neck cancer treated with radiation therapy. Issue 1 (28th July 2016) - Min, Myo; Lin, Peter; Liney, Gary; Lee, Mark; Forstner, Dion; Fowler, Allan; Holloway, Lois
Summary: Advanced radiotherapy techniques, such as intensity‐modulated radiotherapy, have been reported to reduce toxicities by improving the dose conformity in mucosal primary head and neck cancer (MPHNC). However, to further optimize the therapeutic ratio, details on individual patient and disease characteristics may be necessary to tailor treatments. This is likely to include identifying poor responders for treatment intensification and good responders for de‐escalation strategies. Non‐invasive, repeatable imaging biomarkers are attractive modalities in both pre‐treatment and intra‐treatment response prediction with a view to individualized treatment options. This review has assessed the current literature on the prognostic/predictive role of widely available functional imaging (FI) studies such as fMRI(functional magnetic resonance imaging), functional computed tomography (fCT) and positron‐emission‐tomography(PET). A literature search was carried out using Medline, Embase and PubMed. Studies were included if imaging was undertaken pre and/or during radiotherapy (with or without the addition of chemotherapy and/or surgery). A total of 99 relevant studies were identified: 14 fMRI, 10 fCT, 59 FDG‐PET and 16 non‐FDG‐PET studies. These articles were reviewed to identify imaging parameters demonstrating a correlation with patient outcome or a factor considered to impact on patient outcome and thus likely to be of potential predictive value in MPHNC and associated future radiotherapy treatment directions. Several studies have demonstrated that both pre‐treatment and mid‐treatment FDG‐PET is predictive of outcomes. However, further studies are required to confirm the role of other imaging studies including fMRI and PET using other tracers. There is large heterogeneity within and between published studies, including tumour sites, treatment options, outcome endpoints and parameters assessed. We propose a minimum set of factors that should be reported and make recommendations for studies evaluating the predictive utility in MPHNC.